MULTIMODAL ANALYSIS ON ERTIGA CAR ADVERTISEMENT - Herman; Purba, Ridwin (Wiralodra English Journal, 2020)
Language always refers to communication where spoken and written texts are dominated in human’s life. Communication does not always mean verbal but it is also can be visual. Visual (pictures, gestures, photos, advertisement, and so on) also means text and can deliver message as communication to others. Like verbal, visual also has structures how it delivers the message to audience. Advertisements are the visual objects that human always see for they are dominating in television. The purpose of this research is to investigate the structures of advertisement of Ertiga car. Theories to be used are Kress (2009) and Cheong (2004). Descriptive qualitative was conducted in this research. The source data was the advertisement of a car from Suzuki, Ertiga. After analyzing the data, the researchers found that verbal components (Announcement, Enhancer, Emblem, Tag, Cal-and-visit information) and visual components (Lead, Display and Emblem) were inserted in the advertisement of Ertiga. It means that the advertisement of Ertiga is made in a good way where the purpose of advertisement is to persuade the audience to buy the product. In short, the structures of the advertisement determine the quality of the product.